De la teología a la crítica social : preludios antirracistas en la Goa barroca - Ana Isabel López-Salazar (Ler História, 2019)
In mid-seventeenth-century Goa two major socio-religious debates were superimposed : the access to the priesthood of the Brahmins converted to Christianity and the inferior status of the Portuguese friars born in India with respect to those of the kingdom. In this context, an Italian Theatine, who had recently arrived in India, decided to tackle an issue that had been undermined until then : the access to the sacramental communion of the Christians converted from Hinduism and of the black slaves of African origin. In Goa, a clearly European concern – the question of frequent communion – acquired new connotations that allowed Antonio Ardizzone Spinola (1605-1699) to fight against the religious discrimination of slaves and defend the dignity of all Christians, regardless of the color of their skin, and their unrestricted access to the sacraments.